2019
DOI: 10.1093/mnras/stz172
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of supermassive black hole binaries and tidal disruption rates in non-spherical galactic nuclei

Abstract: Binary supermassive black holes (SMBH) are expected to form naturally during galaxy mergers. After the dynamical friction phase, when the two SMBHs become gravitationally bound to each other, and a brief stage of initial rapid hardening, the orbit gradually continues to shrink due to three-body interactions with stars that enter the loss cone of the binary. Using the stellar-dynamical Monte Carlo code RAGA, we explore the co-evolution of the binary SMBH and the nuclear star cluster in this slow stage, for vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 116 publications
(183 reference statements)
2
8
1
Order By: Relevance
“…It is clear from this analysis that mass deficits in triaxial galaxies are smaller than in the spherical geometry, since most stars ejected by the binary are from orbits with very large characteristic radii. The fact that for triaxial systems the hardening of a massive binary is almost entirely driven by draining of centrophilic orbits that arrive from outside the SMBH binary sphere of influence was already noted before (e.g., Vasiliev 2015;Lezhnin & Vasiliev 2019). Here, we have shown that the morphology of a galaxy has a direct impact on the evolution of its nuclear density profile.…”
Section: Time Evolution Of Core Properties and The Effect Of Triaxialitysupporting
confidence: 75%
“…It is clear from this analysis that mass deficits in triaxial galaxies are smaller than in the spherical geometry, since most stars ejected by the binary are from orbits with very large characteristic radii. The fact that for triaxial systems the hardening of a massive binary is almost entirely driven by draining of centrophilic orbits that arrive from outside the SMBH binary sphere of influence was already noted before (e.g., Vasiliev 2015;Lezhnin & Vasiliev 2019). Here, we have shown that the morphology of a galaxy has a direct impact on the evolution of its nuclear density profile.…”
Section: Time Evolution Of Core Properties and The Effect Of Triaxialitysupporting
confidence: 75%
“…More sophisticated techniques, beyond the scope of this paper, can be used for binary BHs (e.g. Lezhnin & Vasiliev 2019), which often result in an increased rate, at least for a short time (e.g. Chen et al 2009Chen et al , 2011Li et al 2017).…”
Section: Tde Ratementioning
confidence: 99%
“…Once the binary forms and hardens, further shrinking the SMBH binary's orbit requires few body interactions that transfer energy and angular momentum to the scattered stars. This few-body scattering phase has been rigorously modeled using a broad range of techniques and underlying assumptions; regardless of the technique, the SMBH binary is either invoked in equilibrium galaxy models (Makino & Funato 2004;Berczik et al 2005Berczik et al , 2006Merritt 2006;Khan et al 2013;Vasiliev et al 2015;Bortolas et al 2016;Gualandris et al 2017;Lezhnin & Vasiliev 2019) or allowed to form self-consistently through galaxy merger simulations (Milosavljević & Merritt 2001;Khan et al 2011;Preto et al 2011;Gualandris & Merritt 2012;Khan et al 2012aKhan et al ,b, 2016Rantala et al 2017;Khan et al 2018a,b). After two decades of work, a converging scenario has emerged: SMBH binaries in the few-body scattering phase continue to shrink at an almost constant rate to a separation where coalescence via gravitational wave emission is inevitable.…”
Section: Introductionmentioning
confidence: 99%